Resting Cyst Distribution and Molecular Identification of the Harmful Dinoflagellate Margalefidinium polykrikoides (Gymnodiniales, Dinophyceae) in Lampung Bay, Sumatra, Indonesia - Thoha, Hikmah; Muawanah; Bayu Intan, Mariana D.; Rachman, Arief; Sianturi, Oksto Ridho; Sidabutar, Tumpak; Iwataki, Mitsunori; Takahashi, Kazuya; Avarre, Jean-Christophe; Masseret, Estelle (Frontiers in Microbiology, 2019)
Margalefidinium polykrikoides, an unarmored dinoflagellate, was suspected to be the causative agent of the harmful algal blooms - associated with massive fish mortalities - that have occurred continually in Lampung Bay, Indonesia, since the first bloom event in October 2012. In this study, after examination of the morphology of putative M. polykrikoides-like cysts sampled in bottom sediments, cyst bed distribution of this harmful species was explored in the inner bay. Sediment samples showed that resting cysts, including several morphotypes previously reported as M. polykrikoides, were most abundant on the northern coast of Lampung Bay, ranging from 20.6 to 645.6 cysts g-1 dry sediment. Molecular phylogeny inferred from LSU rDNA revealed that the so-called Mediterranean ribotype was detected in the sediment while M. polykrikoides motile cells, four-cell chain forming in bloom conditions, belonged to the American-Malaysian ribotype. Moreover, hyaline cysts, exclusively in the form of four-cell chains, were also recorded. Overall, these results unequivocally show that the species M. polykrikoides is abundantly present, in the form of vegetative cells, hyaline and resting cysts in an Indonesian area.